2013
DOI: 10.1016/j.immuni.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

S100A8-S100A9 Protein Complex Mediates Psoriasis by Regulating the Expression of Complement Factor C3

Abstract: Psoriasis is a common heterogeneous inflammatory skin disease with a complex pathophysiology and limited treatment options. Here we performed proteomic analyses of human psoriatic epidermis and found S100A8-S100A9, also called calprotectin, as the most upregulated proteins, followed by the complement component C3. Both S100A8-S100A9 and C3 are specifically expressed in lesional psoriatic skin. S100A9 is shown here to function as a chromatin component modulating C3 expression in mouse and human cells by binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
212
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(233 citation statements)
references
References 49 publications
19
212
1
1
Order By: Relevance
“…The S100A8/A9 complex (also known as calprotectin) was shown to be constitutively expressed in monocytes in various tissues associated with inflammatory processes while weakly expressed in tissue macrophages (35)(36)(37)(38). The expression of this complex was shown to be regulated by lipopolysaccharide (LPS) (39). This result was consistent with our proteomics analysis results (Figs.…”
Section: Analysis Of Protein Expression In Differentiated Monocytes-supporting
confidence: 90%
“…The S100A8/A9 complex (also known as calprotectin) was shown to be constitutively expressed in monocytes in various tissues associated with inflammatory processes while weakly expressed in tissue macrophages (35)(36)(37)(38). The expression of this complex was shown to be regulated by lipopolysaccharide (LPS) (39). This result was consistent with our proteomics analysis results (Figs.…”
Section: Analysis Of Protein Expression In Differentiated Monocytes-supporting
confidence: 90%
“…Enhanced expression of the calcium-binding proteins S100 calcium-binding protein A8 and A9 (S100A8 and S100A9) was observed in human prostate cancer, 20 and Jun/AP-1 controls the S100a8/S100a9 expression in mouse epidermis. 21,22 Increased expression of S100A8 and S100A9 was detected by western blot and IHC in JunB ΔP ; Pten ΔP tumours, while mRNA expression was unchanged (Figure 4a and c). The S100A8-and S100A9-positive cells appeared to be non-epithelial and IHC co-staining with F4/80 indicated that most positive cells were of the monocyte/ macrophage lineage (Figure 4b, Supplementary Figure 4a).…”
Section: Resultsmentioning
confidence: 97%
“…[25][26][27][28] As a general principle, extracellular S100A9 stimulates innate immune cells and endothelial cells, via interactions with the receptor for advanced glycation end products 29 and Toll-like receptor-4 (TLR4), 30 to elicit and augment proinflammatory responses; however, its expression in granulomas as well as its role in granuloma formation have never been addressed. In the present study, we found that neutrophils expressing S100A9 accumulated in the central area of granulomas, and that the S100A9 protein may serve as a key molecule for granuloma formation.…”
Section: Discussionmentioning
confidence: 99%